The Effect of Storage Temperature and Sorbitol Concentration Against the shelf life of strawberry fruit (Fragaria ananassa) - Dyah Roeswitawati; Putri Ayu Lestari; Untung Santoso (Nabatia, 2019)
The purpose of this study was to study the relationship between storage temperature and sorbitol concentration on the shelf life of strawberries. The research was carried out in the Agrotechnology Laboratory of the Faculty of Agriculture-Animal Husbandry, University of Muhammadiyah Malang in October to November 2018. The design of the experiment used a randomized nested design. The first factor is the storage temperature namely T1 (room temperature) and T2 (cold temperature of 100 C), the second factor is sorbitol concentration which is P0 (without treatment), P1 (5%), P2 (10%), P3 (15%), P4 (20%), P5 (25%), the observed variables were weight loss, fruit volume, fruit hardness, percentage of disease severity, disease attack intensity, fruit shelf life, vitamin C content, and total dissolved solids. The results showed no interaction between storage temperature treatment and sorbitol concentration on the shelf life of strawberries. Temperature of 100 C significantly affected the parameters of weight loss, fruit volume, fruit hardness, percentage of disease severity, intensity of disease attack, vitamin C levels, total dissolved solids, and the shelf life of strawberries. The treatment of sorbitol concentration did not significantly affect the parameters of weight loss, fruit volume, fruit hardness, percentage of disease severity, disease intensity, vitamin C levels, total dissolved solids and shelf life of strawberries. Temperature of 100 C is able to maintain the shelf life of fruit up to 14 days, 25% sorbitol concentration is able to extend the shelf life of strawberries at room temperature for 7 days.